Modern slavery challenges to supply chain management - Gold, Stefan; Trautrims, Alexander; Trodd, Zoe (Emerald, 2015)
Purpose – This paper aims to draw attention to the challenges modern slavery poses to supply chain management. Although many international supply chains are (most often unknowingly) connected to slave labour activities, supply chain managers and researchers have so far neglected the issue. This will most likely change as soon as civil society lobbying and new legislation impose increasing litigation and reputational risks on companies operating international supply chains.